Path Analysis: The Effect of Biopsychosocial and Environmental Exposure on Child Asthma in Surakarta - Hadianti, Ayunita Dwi; Budihastuti, Uki Retno; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2016)
Background: Asthma is a non-communicable disease with high morbidity in Indonesia.According to David BarkerÃ¢â¬â¢s fetal origin hypothesis, biopsychosocial as well as environmental exposure during gestational period affect health outcome in later life. This study aimed to determine the effect of bio-psychosocial and environmental exposure factor on the risk of child asthma in Surakarta.Subjects and Methods: This was an analytical observational study with case control design.This study was conducted at the Center for Community Pulmonary Health (BBKPM), Surakarta. A total of 105 study subjects were selected by fixed disease sampling, consisting of 35 asthmatic patients and 70 healthy children aged 6-15 year old. The exogenous variables were maternal education, current child stress, indoor cigarette smoke exposure and maternal stress during gestational period, current family income, and current indoor cigarette smoke exposure. The endogenous variables were birth weight and child asthma. The data were collected by a set of questionnaire and analyzed using path analysis model.Results: Current child stress (b = 3.49; 95% CI = 1.18-5.81; p = 0.003), exposure to indoor cigarette smoke (b = 3.44; 95% CI = 1.07-5.80; p = 0.004), indoor air polution (b = 2.43; 95% CI = 0.60-4.27; p = 0.009), had positive, direct, and statistically significant effects on the risk of child asthma. Birth weight Ã¢â°Â¥2.500 gram (b = -2.01; 95% CI = -3.95 to -0.07; p = 0.041) had negative, direct, and statistically significant effect on the risk of child asthma. Maternal education had positive and statistically significant effect on family income (b=1.57; 95% CI=0.62 to 2.52; p= 0.001). Family income had negative and statistically significant effect on indoor air pollution (b= -2.48; 95% CI=-3.52 to -1.44; p= 0.001). Maternal stress at gestational period had negative and statistically significant effect on birth weight (b=-1.13; 95% CI= -2.18 to -0.08; p=0.035).Conclusion: In line with David BarkerÃ¢â¬â¢s fetal origin hypothesis, this study supports that biopsychosocial as well as environmental factors have significant effects on child asthma.Keywords: bio-psychosocial, environmental exposure, asthma, children.Correspondence:ÃÂ Ayunita Dwi Hadianti. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: ayunitadwihadianti@gmail.com. Mobile: +6282314064445.Journal of Maternal and Child Health (2016), 1(2): 62-72https://doi.org/10.26911/thejmch.2016.01.02.01